A nomogram to predict anastomotic leakage in open rectal surgery: hope or hype? - Klose, Johannes; Tarantino, Ignazio; Kulu, Yakup; Bruckner, Thomas; Volz, Claudia; Schmidt, Thomas; Schneider, Martin; Büchler, Markus W.; Ulrich, Alexis (Journal of gastrointestinal surgery, 2018)
Anastomotic leakage is the most dreaded complication after rectal resection and total mesorectal excision, leading to increased morbidity and mortality. Formation of a diverting ileostomy is generally performed to protect anastomotic healing. Identification of variables predicting anastomotic leakage might help to select patients who are under increased risk for the development of anastomotic leakage prior to surgery. The objective of this study was to assess the applicability of a nomogram as prognostic model for the occurrence of anastomotic leakage after rectal resection in a cohort of rectal cancer patients.